Proceedings of the International Conference on Emerging Trends in Engineering &Amp; Technology (IConETech-2020) 2020
DOI: 10.47412/aabl1209
|View full text |Cite
|
Sign up to set email alerts
|

Linking Sustainable Transport and Community Development: Transportation 2.0 in the Small Island of Tobago

Abstract: Worldwide the UN is promoting sustainable transport that requires the engagement of communities to make it context and community sensitive. To better engage the community, governments started to use web-based social geocommunication tools in urban areas. The use of these tools is increasing; however, it can be critically questioned to what extent they can support sustainable transport development in rural areas in Trinidad and Tobago. To respond to this question, the paper presents preliminary results of an on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Thus, commuters' and travellers' primary mode of transport is the car, or they consider the car as the only acceptable choice in terms of costs, time, safety and prestigious status (Wiersma, 2020). Some remote areas on the islands are only accessible by car, although in some islands the rural population depends on public transport or privately owned mini busses (Kotzebue, 2020). Studies showed that geographical remoteness can be a significant barrier to social inclusion (Cass, Shove, & Urry, 2005;Lucas, Mattioli, Verlinghieri, & Guzman, 2016).…”
Section: Equity and Gendermentioning
confidence: 99%
“…Thus, commuters' and travellers' primary mode of transport is the car, or they consider the car as the only acceptable choice in terms of costs, time, safety and prestigious status (Wiersma, 2020). Some remote areas on the islands are only accessible by car, although in some islands the rural population depends on public transport or privately owned mini busses (Kotzebue, 2020). Studies showed that geographical remoteness can be a significant barrier to social inclusion (Cass, Shove, & Urry, 2005;Lucas, Mattioli, Verlinghieri, & Guzman, 2016).…”
Section: Equity and Gendermentioning
confidence: 99%
“…Thus, commuters' and travellers' primary mode of transport is the car, or they consider the car as the only acceptable choice in terms of costs, time, safety and prestigious status (Wiersma, 2020). Some remote areas on the islands are only accessible by car, although in some islands the rural population depends on public transport or privately owned mini busses (Kotzebue, 2020). Studies showed that geographical remoteness can be a significant barrier to social inclusion (Cass, Shove, & Urry, 2005;Lucas, Mattioli, Verlinghieri, & Guzman, 2016).…”
Section: Equity and Gendermentioning
confidence: 99%
“…Thus, commuters' and travellers' primary mode of transport is the car, or they consider the car as the only acceptable choice in terms of costs, time, safety and prestigious status (Wiersma, 2020). Some remote areas on the islands are only accessible by car, although in some islands the rural population depends on public transport or privately owned mini busses (Kotzebue, 2020). Studies showed that geographical remoteness can be a significant barrier to social inclusion (Cass, Shove, & Urry, 2005;Lucas, Mattioli, Verlinghieri, & Guzman, 2016).…”
Section: Equity and Gendermentioning
confidence: 99%